A historical consideration of seed saving and suggestions for future seed savers - Dostal, Ryan (Kansas State University, 2018)
Seed saving, whether performed by subsistence farmers, by breeders at land grant universities, or the seed industry, provide the world’s farmers with the needed supply of seeds to produce food crops annually. This thesis considers historical agricultural trends as they relate to the process of seed saving. It utilizes information gathered from primary source materials, historical monographs, and FAO and NGO publications. Chapter two discusses six universal agricultural dichotomies and how they relate to seed saving over time and globally. The dichotomies examined as they relate to seed saving include: subsistence and commercial, commons and commodity, public and private, basic and applied, global north and south, and urban and rural food production. Subsistence and commons oriented agricultural systems have historically traveled towards commercial and commodity forms in developed countries like the United States. As a result, seed saving moved from something farmers did to either public or private institutions that performed basic and applied research for genetic improvement of agricultural crops. As breeding programs looked outward for better breeding materials (germplasm) the importance of the Global North and South and Urban and Rural locales became important. Based on the results of this examination, it is clear that prioritizing subsistence practices and understanding seeds as a commonly held resource play important roles in maintaining agricultural diversity, particularly for more commercialized and commodity oriented agricultures. This shift from subsistence to commercial agriculture in the Global South jeopardizes subsistence agriculture’s ability to maintain agricultural diversity. Chapter three utilized a case study framework and focused on American seed saving within the Corn Belt from 1890 to 1950. The Corn Show, a common annual showcase of corn seed savers in the Midwest, supported both subsistence and commercial agricultural ideals. It also set the stage for the introduction of hybrid corn and suggested an alternative to the commodification of seeds by the industry. These results suggest that seed saving programs today could benefit from a culture that values subsistence practices while still utilizing the benefits of contemporary methods that are common to commodification. The added benefit of community and diversity that are realized by seed saving could develop a culture of seed production that is capable of contributing to rural development goals. This thesis concludes by tying together its discussion of dichotomies, reinforcing the connectedness between different agricultural production systems, and thus, the need for many different types of seed saving.
Keywords: Seed saving; Germplasm; History; Urban food systems; Corn show; Agriculture